Singapore's overseas industrial parks ventures. - Chung, Desiree May Hwi. (2008)
This report highlights Singapore's regionalisation and globalisation strategy through the building of industrial parks. Based on the success of past industrial parks ventures, some crucial points are identified as to what determines the success of these projects.